Paediatric obesity and brain functioning: The role of physical activity—A novel and important expert opinion of the European Childhood Obesity Group. Issue 9 (27th May 2020) - Esteban‐Cornejo, Irene; Reilly, John; Ortega, Francisco B.; Matusik, Pawel; Mazur, Artur; Erhardt, Eva; Forslund, Anders; Vlachopapadopoulou, Elpis Athina; Caroli, Margherita; Boyland, Emma; Weghuber, Daniel; Thivel, David
Summary: While most of the time unconsidered, child and adolescent obesity has been also associated with impaired brain health and function that can definitely affect their social interaction and integration, and then well‐being and mental health. The European Childhood Obesity Group recently gathered experts in the field who discussed the main available and reliable evidence regarding the role of physical activity on brain health and cognitive functioning in children and adolescents with obesity and who propose here their main conclusions and recommendations.